DESIGN AND IMPLEMENTATION OF CONTROL SYSTEM FOR PERISTALTIC PUMP IN MICROFLUIDIC PUMP SYSTEM FOR SAMPLE PROCESSING - Kartika Adi, Tripamungkas
When doing experiment using a microfluidic platform, the user needs a pump system to deliver fluids into the platform in the scale of microlitre-to-nanolitre per minute. One example of pump systems which is commonly found in the market is peristaltic pump. The pump needs to be implemented with a control system so it can be used as a system for delivering fluids into the microfluidic platform. In designing a control system for the peristaltic pump, the system can control the average flow rate of the fluids with notable characteristics, for example, the flow generated by peristaltic pump has pulsing characteristics, so the designed system need to be limited of it usages for some scenarios. The designed pump control system can only deliver fluid with minimum accuracy of volume dispensed of 90% after the system has been started for 7 seconds, so the system is not suitable for fluid delivery scenario which need to be accurate and has shorter duration. The pump control system can be used to deliver aquades, PBS with concentration 10 mM, and glucose solution with concentration of 1 mM and 10 mM readily without the need to apply calibration factor, because the difference of values between sensor measurement and manual measurement has only maximum of 2,31%, so it can be used for some scenarios that don’t need very high accuracy of volume dispensed or average flow rate (error less than 1%).